Ordinariness in Disaster: Notes from Rereading Story during the COVID-19 Pandemic - Uyheng, Joshua (Archīum Ateneo, 2020)
In contexts of broad structural strain, humanistic psychology points to the deeply embodied, relational, and spatiotemporal nature of literary encounters by agents in history. Through heuristic inquiry, this essay examines thematic transformations of Rofel G. Brion’s Story (1997), an autobiographical collection of poetry, when reread during the COVID-19 pandemic. I reflect on selected poems to reconsider and reclaim themes of intimacy amid solitude through narrative affection, home in exile through connections of care, and possibilities for living in ordinary time.